PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN ( STUDI KARYAWAN KANTOR PUSAT PTPN V PEKANBARU ) - ", Bernita; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect of Work Environment and Organization Commitment To Job Employees Statisfaction Head Office PTPN V Pekanbaru.This research used questionnaire with measurement scale that is Likert scale which analyzed by validity test, reliability test, simple regression analysis, multiple regression analysis, analysis of determination, t test, and f test with the help of using SPSS software ver. 17 for windows. The number population from this research 478 persons with 83 head office employees PTPN V Pekanbaru as the sampled, calculated using slovin formula.From the results of tests conducted indicate that the Work Environment has a significant effect on employee job satisfaction, Organizational Commitment has a significant effect to employee job statisfaction, as well as Work Environment and Organizational Commitment have a significant effect on employee job statisfaction Head Office in the PTPN V Pekanbaru.Keywords : Work Environment, Organization Commitment, Job Satisfaction.